1084 Cholesterol deficiency associated APOB mutation affects lipid metabolism in Holstein cattle. (1st October 2016) - Gross, J. J.; Schwinn, A. C.; Schmitz-Hsu, F.; Menzi, F.; Drögemüller, C.; Albrecht, C.; Bruckmaier, R. M.
Abstract: During the last months, the number of reports on Holstein calves suffering from incurable idiopathic diarrhea dramatically increased. Affected calves showed severe hypocholesterolemia, and mostly died within days up to a few months after birth. This new autosomal monogenic recessive inherited fat metabolism disorder termed cholesterol deficiency (CD) is caused by a loss of function mutation of the bovine APOB gene. The objective of the present study was to investigate specific components of the lipid metabolism in 6 CD affected homozygous for the APOB mutation (CDS) and six normal Holstein calves with different APOB genotypes. Independent of sex, CD affected calves (CDS) had significantly lower plasma concentrations of total cholesterol (TC), free-cholesterol (FC), high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), very low density lipoprotein-cholesterol (VLDL-C), triacylglycerides (TAG), and phospholipids (PL) compared to homozygous wild-type calves ( P < 0.05). Furthermore, we studied the effect of the APOB genotype on cholesterol metabolism in adult Holstein breeding bulls of Swissgenetics. Among a total of 254 adult males the homozygous mutant genotype was absent, 36 bulls were heterozygous carriers (CDC), and 218 homozygous wild-type (CDF). In CDC bulls, plasma concentrations of TC, FC, HDL-C, LDL-C, VLDL-C, TAG, and PL were lower compared to CDF bulls ( P < 0.05). The ratios of FC:cholesteryl esters (CE), and FC:TC were higher in CDC compared to CDF bulls, whereas the ratio of CE:TC was lower in CDC compared to CDF bulls ( P < 0.01). In conclusion, the cholesterol deficiency associated APOB mutation was shown to affect lipid metabolism in affected Holstein calves and adult breeding bulls. Besides cholesterol also the concentrations of PL, TAG, and lipoproteins were distinctly reduced in homozygous and heterozygous carriers of the APOB mutation. Beyond malabsorption of dietary lipids, deleterious effects of apoB deficiency on hepatic lipid metabolism, steroid biosynthesis, and cell membrane function can be expected, which may result in unspecific symptoms of reduced fertility, growth, and health.